Equivalent synchronization patterns in chaotic jerk systems. (1st July 2022) - Mirzaei, Simin; Parastesh, Fatemeh; Jafari, Sajad; Schöll, Eckehard; Kurths, Jürgen
Abstract: Jerk systems are some of the simplest dynamical systems that can exhibit chaotic dynamics. This paper investigates the synchronization of coupled jerk systems with coupling in single variables. We apply the well-known approach for synchronization analysis, the master stability function, which determines the stability of the synchronization manifold. It is shown that a jerk system in which the jerk equation is not dependent on the acceleration has similar master stability functions when coupled in velocity or acceleration variables. Therefore, the system has the same synchronization behavior in these two coupling configurations. Such an equivalence has not been reported in the literature.